PENGARUH BUDAYA ORGANISASI DAN KOMPENSASI TERHADAP KOMITMEN KARYAWAN KOPERASI MAHASISWA UNIVERSITAS NEGERI YOGYAKARTA - Dwi Novita (JURNAL EKOBIS DEWANTARA, 2018)
The purpose of this research to decribe (1) the effect of organizational culture on employe’scommitment (2) the effect of compenstion on employe’s commitment and (3) the effect oforganizational culture anda compenstion together employe’s commitment of KoperasiMahasiswa Universitas Negeri Yogyakarta.This research is classified in research expostfacto. Variabel in the research is organizational culture, compenstion and employeecommitment. Its population is a 40 employes of Koperasi Mahasiswa Universitas NegeriYogyakarta and sampelas for the stuy of 40 people. Methods of data collection is done byusing the media questionnaries, while data analysis techniques using multiple linearregression analysis. Before doing the analysis in advance to test the prerequisite by classicalassumption test cosisting of normality test, multicoloniarity test, and heterocedastictiytest.The result showed that the multiple lnear regression model is Y= 0,543X1=0,340X2.That’s is, organizational culture (X1) and compenstion (X2) contributes greatly to employesscommitment. T test results prove there is influence between organizational culture variables(X1) and compensation (X2) on employee commitment (Y), with the result singnifikasi value<0.05 is 0,000 X1 and X2 is 0.008. F test results proved no effect simultaneously withsingnifikasi value of 0.05 is 0.000.The magnitude of the effect seen from the coefficient ofdetermination (